Book Review: Grounded Theory in Perspective: - Helen Scott (Grounded Theory Review: An International Journal, 2017)
The grounded theory general method of research was Glaser and Strauss’ response to the problem of “superthink”: the generation of hypotheses in the field of sociology without recourse to data. Glaser and Strauss observed that since such hypotheses were of little relevance, pursuing them wasted resources and had fateful impact on young researchers’ careers. Glaser and Strauss preferred to ground their hypotheses in data that was from the field and was of relevance to their participants. The resultant development of the grounded theory method to maturity has taken decades of dedicated, scholarly endeavour. Glaser explains and examples how this has been achieved in his new book: The grounded theory perspective: Its origins and growth.